Volatility spillover effects in interbank money markets - Ribeiro, P. P.; Curto, J. D. (Review of World Economics, 2017)
Using daily data from 2006 to 2015, this paper applies alternative multivariate GARCH models and a modified version of the spillover index methodology proposed by Diebold and Yilmaz (Int J Forecast 28(1):57–66, 2012) to test the existence of shock and volatility contagion effects across interbank money markets. Overall, we find evidence that money markets are highly interrelated, exhibiting dynamic cross market effects. Moreover, we emphasize the pertinence of conditional covariances and we show that volatility spillovers are time-varying and very responsive to the major economic events, increasing in periods of higher turbulence, which reinforces the importance of closely monitoring the evolution of money markets.